Description Of Divine Images In The Mythology Of Avesta - Rano Urazova; Muhammad Sayfullaev (International Scientific and Current Research Conferences, 2020)
The article analyzes such issues as the introduction of a mythological layer into the religious system of the Avesta, the sacred source of Zoroastrianism, the image of luminous abstract images of the Supreme God Ahura Mazda and the pantheon surrounding him (a system of divine images).